DIVERSITE ET CONFIGURATION DE LA FLORE LIGNEUSE AUTOUR D’UN RUCHER EN ZONE DE TRANSITION FORET-SAVANE DE LA COTE D’IVOIRE - Coulibaly Siendou; Ouattara Djakalia; Edorh Thérès Thérèse; Koudegnan Comlan Mawuss Mawussi; Kamanzi Kagoyire (European Scientific Journal, ESJ, 2013)
The quality of various honeys consumed in the world depends on many biological, climatic, ecological factors, and extraction method. This preliminary study is carried out in the immediate environment of an apiary located in Côte d’Ivoire forest-savanna transition zone, in order to evaluate the state of the woody flora which supports honey production. A surface floristic inventory revealed a richness of 121 woody species, gathered in 103 genus and 45 families. Canonical Correspondence Analysis show that the type of vegetable formation is the medium factor which explains best species distribution, and to release five floristic groups: dense forests, galleries forests, savannas, fallows of savanna and a significant mosaic formed of clear forests, fallow of forest and fields. An average diversity of the flora was noted, as well as the homogeneous distribution of the identified species in the groups. The taking into account of the herbaceous species should make possible to better appreciate the area floristic diversity.